1996
DOI: 10.1111/j.1439-0329.1996.tb00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Capability of the European and North American race of Gremmeniella abietina to hydrolyse polygalacturonic acid in vitro

Abstract: Polygalacturonase was found to be one of the first enzymes secreted by a pathogen during infection. The polygalacturonic-acid hydrolysing activity was compared between the North American and the European race of Gremmeniella abietina in vitro. Isolates were grown in pure pectin media from which the enzyme activity was analysed. Altogether, 29 isolates were tested in hve experiments (experimental runs in a growing chamber). The data were analysed using variance-component models that included fixed-race effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Herron et al 2000). Previous reports (Petäistö and Kajander 1993;Petäistö and Lappi 1996) have proposed that both races (EU and NA) of GAA could potentially secrete at least one enzyme with polygalacturonase activity because G. abietina can grow on a medium with pectin as a sole carbon source. Pectin degradation in the susceptible P. resinosa was also clearly reported using two monoclonal antibodies, JIM-5 and JIM-7, specific to pectin with varying degrees of esterification (Ylimartimo et al 1997).…”
Section: Anti-b-13-glucansmentioning
confidence: 99%
See 1 more Smart Citation
“…Herron et al 2000). Previous reports (Petäistö and Kajander 1993;Petäistö and Lappi 1996) have proposed that both races (EU and NA) of GAA could potentially secrete at least one enzyme with polygalacturonase activity because G. abietina can grow on a medium with pectin as a sole carbon source. Pectin degradation in the susceptible P. resinosa was also clearly reported using two monoclonal antibodies, JIM-5 and JIM-7, specific to pectin with varying degrees of esterification (Ylimartimo et al 1997).…”
Section: Anti-b-13-glucansmentioning
confidence: 99%
“…This pathogen penetrates its hosts through stomata (Ylimartimo et al 1997) but soon has to deal with various cell walls in order to colonize the host further. In vitro studies revealed that G. abietina is surrounded by an extracellular sheath (ES) containing chitin, galactose, proteins, lipids and polygalacturonic acids (Benhamou and Ouellette 1987a,b) and that it could produce several enzymes such as cellulase, glucanase, xylanase and polygalacturonase (Petäistö et al 1992(Petäistö et al , 1994Petäistö and Kajander 1993;Petäistö and Lappi 1996). Using histo-and cytochemical tests, significant progress has been made in understanding host-pathogen interactions involving G. abietina.…”
Section: Introductionmentioning
confidence: 99%
“…xylanase and polygalacturonase (Petäistö et al, 1992(Petäistö et al, , 1994Petäistö and Kajander, 1993;Petäistö and Lappi 1996; which seem essential during this process.…”
Section: The Pathogen Of Study: Gremmeniella Abietina (Lagerb) Moreletmentioning
confidence: 99%